Theoretical and Numerical Modeling of Nonlinear Electromechanics with Applications to Biological Active Media (Communications in Computational Physics, 2018)
We present a general theoretical framework for the formulation of the nonlinearelectromechanics of polymeric and biological active media. The approach developedhere is based on the additive decomposition of the Helmholtz free energy inelastic and inelastic parts and on the multiplicative decomposition of the deformationgradient in passive and active parts. We describe a thermodynamically sound scenariothat accounts for geometric and material nonlinearities. In view of numerical applications,we specialize the general approach to a particular material model accountingfor the behavior of fiber reinforced tissues. Specifically, we use the model to solvevia finite elements a uniaxial electromechanical problem dynamically activated by anelectrophysiological stimulus. Implications for nonlinear solid mechanics and computationalelectrophysiology are finally discussed.